Saving Lives in Small Workshops: A Practical Guide to Safety in Local Bag - Wahyani, Widhy; Eko Budi Santoso; Diah Wilis Lestarining Basuki (Pascasarjana Universitas Mataram, 2025)
This community service project aims to improve the implementation of Occupational Health and Safety (OHS) at the small-scale bag manufacturing business, Rangganesvi, in Malang, Indonesia. The purpose was to identify occupational hazards and implement appropriate interventions based on Indonesian OHS laws and regulations. Field observations and interviews revealed various risks, including mechanical, physical, electrical, chemical, ergonomic, and psychosocial hazards, affecting workers' health and safety. Specific issues included poor ventilation, inadequate lighting, lack of personal protective equipment (PPE), and poor ergonomic practices. Interventions included safety training, hazard identification, PPE provision, and improvement of work environment design. The results indicated that awareness of OHS principles was initially low, but the introduction of ENASE (Effective, Comfortable, Safe, Healthy, Efficient) work systems and safety briefings led to measurable improvements in work conditions. The study concludes that small enterprises require tailored, participatory safety management approaches to prevent workplace accidents and improve employee wellbeing. Systematic hazard assessments and alignment with Indonesian OHS law (UU No. 1 Tahun 1970) are essential to establish a sustainable safety culture in informal industries.